Student support in an open and distance electronic learning (ODeL) context: The experiences of students with disabilities in KwaZulu-Natal - Cebisa, Zwelakhe Erick (International Journal on Open and Distance e-Learning, 2021)
The institutions of higher learning in South Africa and around the globe are under a lot of pressure to provide equal access to all students with diverse learning needs. It is important to realize that students come from diverse backgrounds, which leads to them experiencing the academic support services offered by open and distance e-learning (ODeL) institutions differently. The experiences of students with disabilities (SWDs) were studied through the adoption of the qualitative and interpretivism paradigm to produce data that is rich in insights. The exploratory research design was followed to achieve a better understanding of in-depth information. The research data was collected using the MS Teams platform, which was necessitated by adhering to the strict protocols demanded by the Covid-19 regulations. A small number of study participants were identified and recruited to provide the required in-depth information about the issues explored in the study. Using a purposive and snowball sampling method, 10 ODeL students were drawn as participants. The results revealed that the common denominator and the most important aspect of an ODeL institution is effective student support. The qualitative findings revealed that institutions of higher learning must understand the needs and requirements of SWDs. This study contributes to the literature by providing a better understanding of SWDs’ needs and the proposed reviewed allocation of resources by the university to cater to the SWDs’ needs. The study recommended the development of disability-friendly technology and infrastructure and the strengthening of the safety program for students with albinism.